Synthesis of monoglycerides by esterification of oleic acid with glycerol in heterogeneous catalytic process using tin-organic framework catalyst - Wee, Lik H.; Lescouet, Tristan; Fritsch, Julia; Bonino, Francesca; Rose, Marcus; Sui, Zhijun; Garrier, Eva; Packet, Dirk; Bordiga, Silvia; Kaskel, Stefan; Herskowitz, Moti; Farrusseng, David; et al. (Catalysis Letters, 2013)
Selective synthesis of monoglycerides by esterification of glycerol with fatty acids is a difficult reaction because of immiscibility of reagents and the formation of di- and tri-glyceride by-products. In this work a heterogeneous catalytic process was conceived in which the reactant mixture was homogenized using tert-butanol solvent. Candidate catalysts were screened in the reaction of oleic acid with glycerol. While under such reaction conditions zeolites were rather inactive, metal-organic frameworks and, especially, tin-organic frameworks were found promising. A tin-organic framework (Sn-EOF) was most active and achieved ≥98 % monoglyceride selectivity at 40 % conversion in catalyzing esterification of oleic acid with glycerol at a low reaction temperature of 150 C. Leaching of tin from Sn-EOF catalyst was suppressed by limiting the amount of oleic acid in the starting mixture. Characterization of the acid sites of Sn-EOF by pyridine-chemisorption and FTIR revealed Lewis acidity to be responsible for the catalytic activity. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Esterification; Monoglycerides; Oleic acid; tert-Butanol; Tin-organic framework